EVALUASI PENGALAMAN PENGGUNA FLEXIBLE LEARNING UKSW MENGGUNAKAN METODE USER EXPERIENCE QUESTIONNAIRE PADA PROSES PEMBELAJARAN - Irawan, Frengki; Tambotoh, Johan Jimmy Carter (Universitas Methodist Indonesia, 2024)
Advances in the world of technology today are very rapid, especially in the world of education. Universities and schools definitely need a platform or moodle in the academic learning process, especially at Satya Wacana Christian University. Satya Wacana Christian University is one of the well-known universities and is much sought after by students in Central Java Province and outside Java Island. This campus uses Moodle in its learning process, namely Flexible Learning. Flexible Learning is used to simplify the teaching and learning process. However, Moodle learning, namely Flexible Learning, has not been proven to satisfy users. This journal was formed to test the experiences of using Flexible Learning among SWCU students. This research uses user experience with a questionnaire to determine satisfaction with using Flexible Learning among UKSW students. The research will be carried out using the method of determining the scope of research, literature review, problem analysis, research instruments, determining respondents, measuring UEQ, analyzing test results, and conclusions. The test results in this research involved a total of 50 students as respondents. The evaluation obtained from the research, namely the 6 aspects of the UEQ, can convey the results of measuring user experience and conclude the results of the UEQ.